1968
DOI: 10.1177/004051756803801001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Alkali Treatment on Native and Denatured Proteins

Abstract: The influence of alkali treatment on wool keratin and on silk fibroin was investigated in a medium of K 2 CO 3 at 50° C. It was found that the denaturing action of LiBr affects the reactivity and reactions of the disulfides differently from stretching of the fibers does.Since the sum total of the sulfur-containing amino acids remains constant during alkali treatment of both native and denatured wool, the participation of cystine in the formation of lysinoalanine is excluded. It is suggested that seryl resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Hot alkali treatment of proteins is known to degrade the amino acids cystine (Cys) 2 , lysine (Lys), and serine (Ser), threonine (Thr), and arginine (Arg). (Cys) 2, Lys, and Arg are main participants in the formation of lanthionine, lysinoalanine, and ornithine [18]. Initially strong aqueous alkali can decompose aliphatic disulfides by direct attack of hydroxide ion on sulfur to give thiol (cysteine) and sulfonic acid (cysteic acid residues) as the principal products [19].…”
Section: Keratin Hydrolysate Formationmentioning
confidence: 99%
“…Hot alkali treatment of proteins is known to degrade the amino acids cystine (Cys) 2 , lysine (Lys), and serine (Ser), threonine (Thr), and arginine (Arg). (Cys) 2, Lys, and Arg are main participants in the formation of lanthionine, lysinoalanine, and ornithine [18]. Initially strong aqueous alkali can decompose aliphatic disulfides by direct attack of hydroxide ion on sulfur to give thiol (cysteine) and sulfonic acid (cysteic acid residues) as the principal products [19].…”
Section: Keratin Hydrolysate Formationmentioning
confidence: 99%
“…oxidative scission of the dehydroalanine derivative followed by oxidation. Later, Mellet (1968) also demonstrated that seryl residues could be involved in the formation of «aminoacrylic acid residues, which in turn could combine with lysine to form LAL. Recently, Finley et al (1982) demonstrated that the degree of cysteine oxidation apparently is a key factor in LAL formation.…”
mentioning
confidence: 98%
“…Alkali treatment of proteins has been shown to cause losses in serine, threonine, cystine, arginine, lysine, and an increase in ornithine (Pickering and Li, 1964; Geschwind and Li, 1964;Zeigler et al, 1967;Mellet, 1968;Blackburn, 1968;DeGroot and Slump, 1969; Parisot and Derminot, 1970;Whiting, 1971;Gottschalk, 1972;Provansal et al, 1975). Amino acid residues in proteins undergo racemization in alkaline solution more readily than do the free amino acids.…”
mentioning
confidence: 99%